Educação, sexualidade e divulgação científica : estado da arte das publicações da área 46 da Capes - Silva, Marcia Daiane da (2012)
This paper presents a study of qualitative and quantitative results of the intention the investigate the publication of magazines in the area 46, qualified CAPES, as regards sexuality and education, considering the divergent debate which was established around the terms sex education an sexual orientation. We take this discussion to a content analysis (BARDIN, 1977) and rhetorical argumentation (PERELMAN; OLBRECHTS-TYTECA, 2005) of area 46 in the articles published, considering the following objectives: a) analyzing the content of articles and on the terms that circulate in research involving education and sexuality; b) know how to establish the terms of the debate between sex education and sexual orientation in area 46 publications. The results allow us to consider the low publication of research in education and for the past 10 years, this shows that, despite all the growth in research in the area, especially after the inclusion of the subject in the school curriculum through of PCNs is very necessary to advance in research on sexuality in the areas of education and science education. One factor relevant to the area is the increase in research on gender and sexual diversity, contribute much to the debate and the paradigm shift in the area. The prospect of a historical approach sexuality, social and cultural development is a positive event for a research on human sexuality, but, are still focused on the biological nature of human sexuality, can be seen in the methodology of the research, which mostly focused on the present course biological science. This research confirmed the importance of disseminating scientific research and the need for better circulation of the same.